Pengembangan Media Puzzle Game Materi Gaya Untuk Kelas IV Sekolah Dasar - Rindi Arti Defi; Zainul Abidin; Susilaningsih Susilaningsih (Jurnal Kajian Teknologi Pendidikan, 2021)
Increasing students' understanding can be done by using media game sugam during the learning process. This development aims to produce a media product game sugam(stacking pictures) of material styles that are feasible and attractive to use to facilitate the process of delivering material at the time of learning. In this game, there are challenges that can motivate students. This media is in the form of a puzzle game Sugam(stacking pictures). This development uses a development model according to Lee & Owens. Responses were obtained from media experts and material experts after product trials. The product utilization trial was conducted by all fourth grade students. Overall Media product game sugam (Arrange pictures) suitable for use in learning.